IMPLEMENTASI BUDAYA PERUSAHAAN DAN ETIKA PERUSAHAAN PADA BADAN KREDIT MIKRO - Dimas Imaniar (Majalah Ilmiah DIAN ILMU, 2014)
Based on the results of research that there are several factors affecting the cultural and ethical company pliers ie : able to understand the state of the corporate culture at BKD office Situbondo so many contributing factors that make it last a long time culture . The factors are : ( a) the confidence factor of the boss . This factor is very influential , because these factors all employees can freely provide the creativity that exists within him to work as much as possible and produce work that way either . ( b ) Factors cooperation between old employees and new hires . This factor makes all employees feel comfortable . Usually old employee was acting semenah - menah to new employees and each other down . But it did not happen in this BKD . Good cooperation shown by the old employees and new employees , so that new employees can better understand and convenient to work with the help of long time employees . Tops of these factors do not discriminate employees . ( c ) Factors to be honest with each other and obey the rules . Given the nature of the employee 's be honest and follow the rules , then the job is done running smoothly and discipline this makes work performed by employees that resulted in a positive culture .